Inovasi Pada Produk Tahu Di Dusun Pomo, Desa Ampel, Kecamatan Wuluhan, Kabupaten Jember - Wahyu Pamungkas; Nikita Diana Diningrum; Rellysia Gestania Putri; Rizka Ellafatul; Taufik Rahman; Nanda Widaninggar (JURNAL PENGABDIAN MASYARAKAT (JPM), 2022)
This Community Service aims to add value to the Tofu produced by Mr. Tomo's family from Pomo Hamlet, Ampel Village, Wuluhan District, Jember Regency. This home industry did not yet recognize the importance of product innovation, how to innovate on products, and the implementation of marketing through product packaging in a more attractive manner. In addition, operations and business records had not been carried out in an accountable manner, so that the maximum production capacity had not been achieved. Cost of Goods Sold was calculated simply and potentially inaccurate because it was not properly recorded. Activities were carried out through product innovation counseling; assistance in making packaging designs, both from the type of container and logo; as well as assistance on how to make Tofu Kress as a result of innovation. The next activity was carried out through Business Analysis, both from the production and financial aspects, to be able to find out the allocation of capital and profits generated after the innovation of “Tahu Kress”. As a result, Mr. Tomo's family significantly understands the importance of product innovation, was able to implement value added to Tofu products by making Tofu Kress, placing it in containers with up-to-date designs, and conducting business analysis on production and financial aspects to develop the production of Tofu in a sustainable manner.